Pengaruh Kepemilikan Manajerial, Growth Opportunities, dan Leverage terhadap Konservatisme Akuntansi Perusahaan Non Keuangan : Studi Empiris pada Perusahaan yang Terdaftar di Bursa Efek Indonesia Periode 2022–2024 - Azra Nurul Atthahirah; Rini Indriani (Jurnal Literasi Akuntansi, 2026)
Purpose: This study aims to examine the effect of managerial ownership, growth opportunities, and leverage on accounting conservatism in corporate financial reporting among non-financial companies listed on the Indonesia Stock Exchange during the 2022–2024 period. Method: This research employs a quantitative approach using secondary data obtained from annual financial reports. The population consists of all non-financial companies listed on the Indonesia Stock Exchange, with samples selected through purposive sampling based on specific criteria. Data analysis is conducted using multiple linear regression, supported by classical assumption tests to ensure the validity and reliability of the regression model. Accounting conservatism is measured using the CONNAC (accrual-based measure), while managerial ownership, growth opportunities, and leverage serve as independent variables. Finding: The results indicate that managerial ownership and growth opportunities have a positive and significant effect on accounting conservatism, suggesting that companies with higher managerial shareholding and stronger growth prospects tend to apply more conservative accounting practices. In contrast, leverage shows a positive but not significant effect, indicating that the level of debt does not significantly influence the application of accounting conservatism. Novelty: This study provides empirical evidence on the determinants of accounting conservatism in emerging markets, particularly Indonesia, by integrating managerial ownership, growth opportunities, and leverage within a single research model and employing the CONNAC proxy as a measurement approach.